2005
DOI: 10.1103/physrevb.72.205406
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb screening and electronic instabilities of small-diameter (5,0) nanotubes

Abstract: We investigate the instabilities that may lead to the breakdown of the Luttinger liquid in the small-diameter ͑5,0͒ nanotubes, paying attention to the competition between the effective interaction mediated by phonon exchange and the Coulomb interaction. We use bosonization methods to achieve an exact treatment of the Coulomb interaction at small momentum transfer, and apply next renormalization group methods to analyze the low-energy behavior of the electron system. This allows us to discern the growth of seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…36 They showed that the appearance of the strongest relevant instability in the (5,0) nanotube is dependent on the dielectric constant of the environment. Hence the appearance of superconductivity for an array of (5,0) carbon nanotubes, in contrast to that for a single (5,0) nanotube, is potentially possible.…”
Section: Relevant Theoretical Studiesmentioning
confidence: 99%
“…36 They showed that the appearance of the strongest relevant instability in the (5,0) nanotube is dependent on the dielectric constant of the environment. Hence the appearance of superconductivity for an array of (5,0) carbon nanotubes, in contrast to that for a single (5,0) nanotube, is potentially possible.…”
Section: Relevant Theoretical Studiesmentioning
confidence: 99%
“…[27][28][29] It is worthwhile to recall that each individual carbon nanotube is itself composed by two coupled ͑identical͒ Luttinger liquids, since there is a left and a right branch, respectively, around each of the two Fermi points. 14,18,30 This implies that the critical exponent governing the decay of the correlation functions in these systems is actually one half the exponents defined in Eqs. ͑27͒.…”
Section: ͑19͒mentioning
confidence: 99%
“…Typical metallic nanotubes correspond to armchair ͑10, 10͒ geometry ͑i.e. radius R Ϸ 7 Å͒ with length L ϳ 1 m. The strength of the density-density Coulomb interactions is then 18,30 …”
Section: ͑19͒mentioning
confidence: 99%
“…An alternative way of reducing interactions, and one which will work for a CNT of any radius, is through screening by, for example, placing the CNT near a metallic plate or within a CNT bundle. 30,31 Therefore, despite neglecting electron-electron interactions, there are several realistic situations in which Eq. ͑4͒ is a reasonable approximation.…”
Section: The Modelmentioning
confidence: 99%